Impact of socio economic factors to changing energy consumption expenditure of the rural sector (with special reference to arachchikattuwa divisional secretariat division) - Kumari, K.H.M.S.K.; Balasooriya, B.S.K. (University of Jaffna, 2014)
Energy is an essential requirement for today’s day to day life. It is necessary to all of us for lighting, cooking, transportation, health service and fulfilling many of our basic needs. Choices of energy sources in a household are affected by many reasons. The main Objective of the study was to study the impact of the socio economic factors on the energy consumption of the rural households. Primary data were collected using questionnaires filled by the rural sector using 50 households in Puttalam district. The secondary data were collected using books, magazines, central bank reports. The multiple regression model and Chi-square test were used to analysis the data. There were 92% of electricity users in rural sector. Considering the Per Capita Energy Consumption Expenditure in rural sector, it was recorded as Rs.596.36. Energy expenditure of the rural sector households was Rs. 2481. Kerosene usage and dry cell battery usage were high in the rural sector. Solar power, which was used by 8% of the households in the rural sector. Lack of an electricity connection also contributes to lower energy spending among the rural poor. According to the survey results, number of family members, monthly income, Ownership of vehicles, education level of the head of family, number of school children, Types of vehicle were the significant factors to changing energy consumption expenditure of households in rural sector. Government should identify the possibilities to develop sustainable energy sources such as wind and solar and should introduce alternative energy sources to reduce the cost.
Keywords: Per capita energy consumption; Household energy usage; sustainable energy sources